Husband's Supportive Relationship and Mother-Fetus Love Bonds on Mother's Anxiety During Pregnancy - Karnoni, Fara; Misrawati, Misrawati; Dewi, Yulia Irvani (CV. Rayyan Dwi Bharata, 2024)
Anxiety in pregnancy is an emotional state that issimilar to anxiety in general but differs in that it specifically focuses on concerns about pregnant women. Anxiety can get worse if a pregnant women experiences fear about the changes that occur in her bodt, the condition of fetus she is carrying and her mental readiness to face the birthing process. This research aimed to find out the correlation between the husband’s support and the maternal-fetal bond towards out the mother’s anxiety in undergoing pregnancy in the work area of Rejosari Community Health Center. This research used descriptive correlational design by employing cross sectional approach. The research samples were 95 respondents that were selected by using purposive sampling technique. This research used husband’s support, Prenatal Attachment Inventory (PAI), and Pregnancy-Related Anxiety Questionnaire-Revised 2 (PRAG-R2). The analysis used was bivariate analysis by using chi-square test. The research results showed that there was a significant correlation between the husband’s support for pregnant women’s anxiety and the research results also showed that there was a significant correlation between the maternal-fetal bond and pregnant women’s anxiety.